Design and Manufacture of a Centrifugal Water Pump with a Circular Casing - INEGBEDİON, Francis and OKONKWO, Chidiebele Nnadike and NDIFE, Joseph Okechukwu (International Journal of Computational and Experimental Science and Engineering, 2021)
A pump is a machine that imparts mechanical energy to a fluid flowing through it, to move it from one point to another. This paper reports the design, manufacture and testing of a centrifugal water pump having a circular casing. A single stage, end suction centrifugal pump designed and manufactured, using locally sourced materials. This pump finds application in homes, agriculture and industries. It consists of an impeller, shaft, suction and delivery pipes and an electric motor. Experiments performed with this pump shows that it can deliver 0.0045m3 of water per second with a pressure head of 34.7m. A 2.5kW electric motor running at a speed of 2900rpm was used to drive the pump.